Who Benefits from Local Oil and Gas Employment? Labor Market Composition in the Oil and Gas Industry in Texas - Zhengyu Cai; Karen Maguire; John V. Winters (Global Labor Organization (GLO), 2018)
This paper examines local labor market outcomes from an oil and gas boom. We examine two main outcomes across gender, race, and ethnicity: the probability of employment in the oil and gas industry and the log wages of workers employed outside the oil and gas industry. We find that men and women both gain employment in the oil and gas industry during booms, but such gains are much larger for men and are largest for black and Hispanic men. We also find positive income spillovers for workers in other industries that are similar in magnitude across demographic groups.
Keywords: J20; Q33; Q40; R10; 330; Oil; Natural Gas; Employment; Gender; Race; Energy